Gender differences in students' attitude towards mathematics at UiTM Terengganu / Zamzulani Mohamed ... [et al.] - Mohamed, Zamzulani; A. Rashid, Ruzaidah; Muda @ Yusof, Nazuha; Abdul Karim, Zokree (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
This study aims to investigate the potential impact of gender in students' attitude towards Mathematics among students in UiTM Terengganu. A random sampling of 86 students have been selected for this study. Independent sample t-test was used to examine the effect of gender on students' attitude towards Mathematics. The finding concluded that there is no significant difference in students' attitude towards Mathematics between gender. Even though there is no difference between gender, the study found that the students' attitude towards Mathematics is considered as not very satisfactory. Therefore, the management of the university should focus on the empowerment of students' attitude to improve the quality of students' achievement in Mathematics.